Preparation process of cork rubber metal composite material
Through the modification of chemical coupling agent and plasma surface treatment technology, the problems of insufficient interface bonding and limited mechanical properties of cork rubber metal composite materials are solved, which significantly improves the bonding strength, mechanical properties and environmental adaptability of the material. It is suitable for Various industrial applications.
Patent Information
- Application Number
- CN202411364153.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-28
- Publication Date
- 2024-12-17
AI Technical Summary
The existing cork rubber metal composite materials have shortcomings in interface bonding performance, mechanical properties and environmental stability, especially in high temperature and high humidity environments.
Using modified chemical coupling agents and plasma surface treatment technology, the interfacial adhesion, overall mechanical strength and environment of the material are significantly improved through cleaning treatment, plasma treatment, modification coupling agent coating and hot pressing molding. Adaptability.
It significantly improves the interface bonding strength, tensile strength and fatigue resistance of composite materials, improves thermal stability and environmental adaptability, extends service life, simplifies production processes, reduces costs, and is suitable for large-scale industrial applications.
Smart Images

Figure CN119142007A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of material science, and in particular to a preparation process of a cork-rubber-metal composite material. Background Art
[0002] Cork-rubber-metal composites have broad application prospects in many industrial fields, such as automobiles, construction, and aviation, and are mainly used for sound insulation, shock absorption, and structural support. However, the existing technology faces some urgent problems in the manufacture of cork-rubber-metal composites, mainly in terms of the interface bonding performance between materials, overall mechanical properties, and environmental stability.
[0003] In traditional composite materials, the interfacial adhesion between metal, cork and rubber is insufficient, which often leads to delamination and peeling, limiting the application life and reliability of the material. This is mainly due to the large differences in physical and chemical properties between the materials, making it difficult to form a stable bond. At the same time, the adhesives used in existing processes are mostly unmodified traditional coupling agents. Although they can improve the bonding strength to a certain extent, their effect is limited, especially in harsh environments such as high temperature and high humidity, where the performance is poor. In addition, traditional surface treatment methods usually cannot effectively improve the interfacial activity of the material, making it difficult for the coupling agent to fully play its role, thereby limiting the overall performance improvement of the composite material. Summary of the invention
[0004] In view of the shortcomings of the prior art, the present invention provides a preparation process of a cork-rubber-metal composite material, which solves the problems of insufficient interface bonding, limited mechanical properties and weak environmental stability of the cork-rubber-metal composite material in the prior art. By introducing modified chemical coupling agents and plasma surface treatment technology, the interface bonding force, overall mechanical strength and environmental adaptability of the composite material are significantly improved.
[0005] To achieve the above objectives, the present invention is implemented by the following technical scheme: A preparation process of a cork-rubber-metal composite material comprises the following steps:
[0006] S1. Clean metal, cork and rubber surfaces;
[0007] S2, plasma treatment of metal, cork and rubber surfaces;
[0008] S3, preparing a modified chemical coupling agent and applying it on metal, cork and rubber surfaces;
[0009] S4, performing hot pressing forming, laminating the metal, rubber and cork and performing hot pressing treatment;
[0010] S5. Cooling treatment to obtain the cork-rubber-metal composite material.
[0011] Preferably, the metal surface cleaning treatment comprises cleaning with an alkaline solution at a temperature of 20-30° C., followed by rinsing with distilled water.
[0012] Preferably, the plasma treatment is performed using argon plasma, the treatment time is 1-3 minutes, and the power is set to 100-300W.
[0013] Preferably, the modified chemical coupling agent comprises:
[0014] 3-Methylpropanetriethoxysilane 70-80wt%;
[0015] Diisocyanate silicone oil 10-20wt%;
[0016] Polyethylene glycol 5-10wt%;
[0017] Dimethyldiallylammonium chloride 2-5wt%.
[0018] Preferably, the preparation method of the modified chemical coupling agent comprises:
[0019] Mixing a silane coupling agent, a reinforcing agent, a surfactant and a catalyst according to a proportion;
[0020] Stir the reaction at 70-90°C for 3-5 hours;
[0021] After the reaction, the mixture is cooled to room temperature and filtered to obtain the modified chemical coupling agent.
[0022] Preferably, the coupling agent application step comprises soaking the metal, cork and rubber in a coupling agent solution with a concentration of 1-3% for 5-15 minutes, followed by drying at room temperature for 1-2 hours.
[0023] Preferably, the thermoforming step comprises:
[0024] Arrange metal, rubber, and cork in stacking order;
[0025] At a temperature of 140-180°C, a pressure of 4-8 MPa is applied for pressing for 10-20 minutes.
[0026] Preferably, the cooling treatment is natural cooling to room temperature at room temperature.
[0027] Preferably, the chemical bonds formed by the modified chemical coupling agent on the surfaces of metal, cork and rubber include complex bonds and covalent bonds.
[0028] Preferably, the thickness of the cork-rubber-metal composite material after hot pressing is 2-10 mm.
[0029] The present invention provides a preparation process of a cork-rubber-metal composite material, which has the following beneficial effects:
[0030] 1. The present invention significantly improves the interfacial bonding strength of the cork-rubber-metal composite material by using modified chemical coupling agents and plasma surface treatment technology, and enhances the overall mechanical properties, including tensile strength and fatigue resistance. In addition, this method also improves the thermal stability and environmental adaptability of the material, enabling it to maintain stable performance under more stringent environmental conditions. The improved production process optimizes processing performance, simplifies the production process, and reduces costs, making the composite material more suitable for large-scale industrial applications, and has significant market application value and technological advancement significance.
[0031] 2. The present invention significantly improves the interfacial bonding strength of the cork-rubber-metal composite material by using a modified chemical coupling agent and plasma surface treatment. Plasma treatment enhances the chemical activity of the material surface, provides more anchoring points for the coupling agent, and enables it to form a more stable chemical bond with the material surface. The components in the modified chemical coupling agent, such as diisocyanate-based silicone oil, react with free radicals in rubber and cork to form a cross-linked structure, which enhances the bonding force between the layers and effectively prevents interlayer peeling.
[0032] 3. The preparation process of the present invention can significantly improve the overall mechanical properties of the composite material, including tensile strength and fatigue resistance. The stable chemical cross-linking network formed by the modified chemical coupling agent between the layers of the material significantly improves the mechanical strength and durability of the material, enabling the composite material to withstand higher mechanical loads and longer cyclic stress, thereby extending its service life.
[0033] 4. The present invention significantly improves the thermal stability of the composite material through the use of plasma treatment and modified chemical coupling agents. Plasma treatment increases the reactivity of the material surface, allowing the coupling agent to react with the material surface more effectively, while the special components in the modified coupling agent enhance the heat resistance of the material, increase the thermal decomposition temperature and melting temperature, so that the composite material can maintain stable performance at higher temperatures.
[0034] 5. The composite material of the present invention exhibits good environmental adaptability, including excellent anti-aging and environmental factor erosion resistance. The use of modified chemical coupling agents significantly improves the performance stability of the material in various harsh environments (such as high humidity and ultraviolet radiation), thereby adapting to a wider range of application environments and more demanding working conditions.
[0035] 6. The composite material preparation process of the present invention simplifies the production process and optimizes the processing performance. The use of plasma treatment and modified coupling agent simplifies the material surface treatment steps, reduces production costs, and improves production efficiency. The optimization of this preparation process makes the composite material more suitable for large-scale industrial production and has a high market application value. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 It is a schematic diagram of the process flow of the present invention. DETAILED DESCRIPTION
[0037] The following will be combined with the drawings in the specification of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0038] Please refer to the attached Figure 1 The embodiment of the present invention provides a preparation process of a cork-rubber-metal composite material, which can prepare a composite material with excellent interface bonding, good mechanical strength and environmental adaptability by optimizing the interface treatment of the material, utilizing a modified chemical coupling agent and precise hot pressing control.
[0039] Material selection:
[0040] Metal materials: First, clean the metal surface with an alkaline solution (pH about 11) at 20-30°C to remove oil and oxide layers, then rinse thoroughly with distilled water.
[0041] Cork material: Choose natural cork, which has excellent sound insulation and shockproof properties. The cork is physically removed of surface impurities and air-dried at room temperature.
[0042] Rubber material: Natural rubber is used because of its good elasticity and wear resistance. The rubber surface is cleaned with warm water and dried.
[0043] Plasma treatment:
[0044] The cleaned metal, cork and rubber surfaces are treated with argon plasma for 1-3 minutes at a power of 100-300 W. This step can increase the roughness and activity of the material surface, which helps the subsequent adhesion of the coupling agent.
[0045] Plasma treatment not only removes contaminants from the material surface, but also introduces new functional groups (such as hydroxyl and carboxyl groups) on the surface, which can enhance the adhesion of subsequent coupling agents.
[0046] For metal surfaces: Argon plasma enhances the complexing reaction ability between the metal surface and the silane groups in the coupling agent by introducing polar functional groups such as hydroxyl groups, thereby improving the bonding strength between the metal and rubber / cork interface.
[0047] For cork and rubber surfaces: Plasma treatment also increases the activity of the surfaces of these materials, allowing modified chemical coupling agents to bind to these surfaces more effectively and promoting chemical cross-linking between different materials.
[0048] Preparation and application of modified chemical coupling agents
[0049] Recipe composition:
[0050] 3-Methylpropanetriethoxysilane: 70-80wt%, as the main surfactant, providing complexation reaction with the metal surface.
[0051] Diisocyanate silicone oil: 10-20wt%, forms chemical bonds with rubber molecules to enhance bonding strength.
[0052] Polyethylene glycol: 5-10wt%, improves the wettability of the overall solution and the diffusion ability on the cork surface.
[0053] Dimethyldiallylammonium chloride: 2-5wt%, accelerates the coupling reaction.
[0054] Preparation method of modified chemical coupling agent: Mix all components evenly at 70-90°C and react for 3-5 hours under stirring to ensure sufficient reaction. After the reaction is completed, cool at room temperature and filter to remove unreacted macromolecules or impurities.
[0055] Application of modified chemical coupling agent: Soak metal, cork and rubber materials in 1-3% modified chemical coupling agent solution for 5-15 minutes. After treatment, dry the materials at room temperature for 1-2 hours to remove the solvent.
[0056] By introducing 3-methylpropane triethoxysilane, diisocyanate silicone oil, polyethylene glycol and dimethyldiallylammonium chloride, the present invention creates a coupling agent with high specificity and reactivity, which can simultaneously form stable chemical bonds with metal, rubber and cork surfaces.
[0057] The specific performance is as follows:
[0058] Complexation reaction: Silane groups react with hydroxyl groups on the metal surface to form a stable complex. This chemical bond greatly improves the bonding strength between the metal and other layers.
[0059] Chemical cross-linking: Diisocyanate-based silicone oil reacts with the free radicals of the rubber to form a reinforced cross-linked network, which not only improves the interfacial bonding strength but also enhances the overall mechanical properties of the composite material.
[0060] Improved wettability: The addition of polyethylene glycol improves the wetting and diffusion of the coupling agent on the cork surface, ensuring a more uniform coating, thereby optimizing the bond between cork and rubber.
[0061] Thermoforming:
[0062] The materials are stacked in the order of metal / rubber / cork, and then pressed at 140-180°C for 10-20 minutes under a pressure of 4-8 MPa. Under this condition, the coupling agent forms complex bonds and covalent bonds between the metal, cork and rubber, thereby improving the bonding strength of the interface.
[0063] The controlled hot pressing molding conditions (140-180°C, 4-8MPa, 10-20 minutes) ensure the sufficient chemical reaction of the coupling agent at the interface of each material, while avoiding the degradation of material properties that may be caused by excessive heating.
[0064] During the hot pressing process, the modified coupling agent forms stable chemical bonds between metal, rubber and cork under high temperature and pressure. These bonds include complex bonds and covalent bonds, which effectively prevent interlayer delamination.
[0065] Appropriate temperature and pressure ensure uniform reaction inside the material, avoid the generation of hot spots and stress concentration, and improve the overall durability and mechanical properties of the composite material.
[0066] Cooling treatment:
[0067] After hot pressing, the material is naturally cooled to room temperature to ensure that the internal stress of the material is released, thereby maintaining the dimensional stability and structural integrity of the composite material.
[0068] The composite material of the present invention exhibits excellent mechanical properties and enhanced durability, and the chemical bonds formed by the coupling agent between different materials significantly improve the overall performance of the composite material. In particular, the use of the modified chemical coupling agent effectively prevents delamination and peeling between materials by forming stable chemical bonds on the surfaces of different materials, and is suitable for industries such as automobiles, construction and aviation, especially in applications requiring excellent sound insulation, shock absorption and durability.
[0069] The innovation of this technical solution lies in the use of a specific modified chemical coupling agent formula and precisely controlled processing conditions to achieve the preparation of high-performance cork-rubber-metal composite materials.
[0070] In order to better understand the present invention, the above method is described in detail below in conjunction with specific embodiments.
[0071] Example 1: Preparation of aluminum-natural rubber-cork composite material
[0072] Steps and parameters:
[0073] 1. Cleaning:
[0074] Metal (aluminum plate): Clean with an alkaline solution of pH 11 at 25°C for 10 minutes, followed by thorough rinsing with distilled water.
[0075] Cork and rubber: Wash in warm water and air dry.
[0076] 2. Plasma treatment:
[0077] Processing materials: aluminum plate, cork, rubber
[0078] Conditions: Argon plasma, power 200 W, treatment time 2 minutes.
[0079] 3. Coupling agent coating:
[0080] Components: 3-methylpropanetriethoxysilane (75 wt%), diisocyanate silicone oil (15 wt%), polyethylene glycol (8 wt%), and dimethyldiallylammonium chloride (2 wt%).
[0081] Preparation: After mixing, react at 80°C for 4 hours, cool and filter.
[0082] Application: Soak metal, cork and rubber in 2% coupling agent solution, treat for 10 minutes and dry for 1.5 hours.
[0083] 4. Hot pressing:
[0084] Temperature: 160℃
[0085] Pressure: 6MPa
[0086] Time: 15 minutes
[0087] 5. Cooling treatment:
[0088] Cool naturally to room temperature.
[0089] Example 2: Preparation of stainless steel-synthetic rubber-cork composite material
[0090] Steps and parameters:
[0091] 1. Cleaning:
[0092] Metal (stainless steel plate): cleaned with an alkaline solution of pH 11 at 30°C for 10 minutes, followed by rinsing with distilled water.
[0093] Cork and synthetic rubber: Wash in warm water and air dry.
[0094] 2. Plasma treatment:
[0095] Processing materials: stainless steel plate, cork, synthetic rubber
[0096] Conditions: Argon plasma, power 250 W, treatment time 2.5 minutes.
[0097] 3. Coupling agent coating:
[0098] Components: 3-methylpropanetriethoxysilane (78 wt%), diisocyanate silicone oil (12 wt%), polyethylene glycol (7 wt%), and dimethyldiallylammonium chloride (3 wt%).
[0099] Preparation: After mixing, react at 85°C for 4.5 hours, cool and filter.
[0100] Application: Soak metal, cork and rubber in 2.5% coupling agent solution, treat for 12 minutes and dry for 2 hours.
[0101] 4. Hot pressing:
[0102] Temperature: 170℃
[0103] Pressure: 5MPa
[0104] Duration: 18 minutes
[0105] 5. Cooling treatment:
[0106] Cool naturally to room temperature.
[0107] Example 3: Preparation of titanium-EPDM rubber-cork composite material
[0108] Steps and parameters:
[0109] 1. Cleaning:
[0110] Metal (titanium plate): cleaned with an alkaline solution of pH 11 at 20°C, followed by rinsing with distilled water.
[0111] Cork and EPDM rubber: Wash with warm water and air dry.
[0112] 2. Plasma treatment:
[0113] Processing materials: titanium plate, cork, EPDM rubber
[0114] Conditions: Argon plasma, power 300 W, treatment time 3 minutes.
[0115] 3. Coupling agent coating:
[0116] Components: 3-methylpropanetriethoxysilane (80 wt%), diisocyanate silicone oil (10 wt%), polyethylene glycol (5 wt%), and dimethyldiallylammonium chloride (5 wt%).
[0117] Preparation: After mixing, react at 70°C for 5 hours, cool and filter.
[0118] Application: Soak metal, cork and rubber in 1.5% coupling agent solution, treat for 5 minutes and dry for 1 hour.
[0119] 4. Hot pressing:
[0120] Temperature: 180℃
[0121] Pressure: 8MPa
[0122] Time: 10 minutes
[0123] 5. Cooling treatment:
[0124] Cool naturally to room temperature.
[0125] Example 4: Preparation of aluminum-silicone rubber-cork composite material
[0126] Steps and parameters:
[0127] 1. Cleaning:
[0128] Metal (aluminum plate): Clean with an alkaline solution of pH 11 at 30°C for 15 minutes, followed by thorough rinsing with distilled water.
[0129] Cork and silicone: Wash in warm water and air dry.
[0130] 2. Plasma treatment:
[0131] Processing materials: aluminum plate, cork, silicone rubber
[0132] Conditions: Argon plasma, power 250 W, treatment time 1.5 minutes.
[0133] 3. Coupling agent coating:
[0134] Components: 3-methylpropanetriethoxysilane (74 wt%), diisocyanate silicone oil (16 wt%), polyethylene glycol (6 wt%), and dimethyldiallylammonium chloride (4 wt%).
[0135] Preparation: After mixing, react at 90°C for 3 hours, cool and filter.
[0136] Application: Soak metal, cork and rubber in 3% coupling agent solution, treat for 15 minutes and dry for 2 hours.
[0137] 4. Hot pressing:
[0138] Temperature: 150℃
[0139] Pressure: 7MPa
[0140] Time: 20 minutes
[0141] 5. Cooling treatment:
[0142] Cool naturally to room temperature.
[0143] Example 5: Preparation of copper-natural rubber-cork composite material
[0144] Steps and parameters:
[0145] 1. Cleaning:
[0146] Metal (copper plate): Clean with an alkaline solution of pH 11 at 25°C for 10 minutes, followed by thorough rinsing with distilled water.
[0147] Cork and natural rubber: Wash in warm water and air dry.
[0148] 2. Plasma treatment:
[0149] Processing materials: copper plate, cork, natural rubber
[0150] Conditions: Argon plasma, power 100 W, treatment time 2 minutes.
[0151] 3. Coupling agent coating:
[0152] Components: 3-methylpropanetriethoxysilane (77 wt%), diisocyanate silicone oil (13 wt%), polyethylene glycol (7 wt%), and dimethyldiallylammonium chloride (3 wt%).
[0153] Preparation: After mixing, react at 85°C for 4 hours, cool and filter.
[0154] Application: Soak metal, cork and rubber in 2.5% coupling agent solution, treat for 10 minutes and dry for 1.5 hours.
[0155] 4. Hot pressing:
[0156] Temperature: 170℃
[0157] Pressure: 5MPa
[0158] Time: 15 minutes
[0159] 5. Cooling treatment:
[0160] Cool naturally to room temperature.
[0161] Comparative Example 1-1:
[0162] The difference from Example 1 is that the aluminum-natural rubber-cork composite material is not subjected to plasma treatment, and the remaining steps are the same as those of Example 1.
[0163] Comparative Example 1-2:
[0164] The difference from Example 2 is that the stainless steel-synthetic rubber-cork composite material is not subjected to plasma treatment, and the remaining steps are the same as those in Example 2.
[0165] Comparative Examples 1-3:
[0166] The difference from Example 3 is that the titanium-EPDM rubber-cork composite material is not subjected to plasma treatment, and the remaining steps are the same as those in Example 3.
[0167] Comparative Examples 1-4:
[0168] The difference from Example 4 is that the aluminum-silicone rubber-cork composite material is not subjected to plasma treatment, and the remaining steps are the same as those of Example 4.
[0169] Comparative Examples 1-5:
[0170] The difference from Example 5 is that the copper-natural rubber-cork composite material is not subjected to plasma treatment, and the remaining steps are the same as those in Example 5.
[0171] Comparative Example 2-1:
[0172] The difference from Example 1 is that: the aluminum-natural rubber-cork composite material is used; an unmodified traditional coupling agent (containing only 3-methylpropanetriethoxysilane) is used, and the remaining steps are the same as those in Example 1.
[0173] Comparative Example 2-2:
[0174] The difference from Example 2 is that: a stainless steel-synthetic rubber-cork composite material is used; an unmodified traditional coupling agent is used, and the remaining steps are the same as those in Example 2.
[0175] Comparative Example 2-3:
[0176] The difference from Example 3 is that: titanium-EPDM rubber-cork composite material; unmodified traditional coupling agent is used, and the remaining steps are the same as those in Example 3.
[0177] Comparative Examples 2-4:
[0178] The difference from Example 4 is that: the aluminum-silicone rubber-cork composite material; the unmodified traditional coupling agent is used, and the remaining steps are the same as those of Example 4.
[0179] Comparative Examples 2-5:
[0180] The difference from Example 5 is that: the copper-natural rubber-cork composite material; an unmodified traditional coupling agent is used, and the remaining steps are the same as those in Example 5.
[0181] Comparative Example 3-1:
[0182] The difference from Example 1 is that: the aluminum-natural rubber-cork composite material; no coupling agent is used, and the remaining steps are the same as those in Example 1.
[0183] Comparative Example 3-2:
[0184] The difference from Example 2 is that: the stainless steel-synthetic rubber-cork composite material is used; no coupling agent is used, and the remaining steps are the same as those in Example 2.
[0185] Comparative Example 3-3:
[0186] The difference from Example 3 is that: the titanium-EPDM rubber-cork composite material; no coupling agent is used, and the remaining steps are the same as those in Example 3.
[0187] Comparative Examples 3-4:
[0188] The difference from Example 4 is that: the aluminum-silicone rubber-cork composite material; no coupling agent is used, and the remaining steps are the same as those of Example 4.
[0189] Comparative Examples 3-5:
[0190] The difference from Example 5 is that: the copper-natural rubber-cork composite material; no coupling agent is used, and the remaining steps are the same as those in Example 5.
[0191] Comparative experiment 1: Interface bonding strength test
[0192] Experimental steps:
[0193] 1. Sample preparation:
[0194] Composite material samples were prepared according to the preparation process of Examples 1-5 and Comparative Examples 1-1 to 3-5, and each sample had a size of 50 mm x 50 mm x 5 mm.
[0195] 2. Sample installation:
[0196] Install the sample in the peel test fixture or shear test fixture of the universal materials testing machine, making sure the sample is firmly fixed.
[0197] 3. Test condition settings:
[0198] The stretching speed was set to 10 mm / min.
[0199] The test temperature was set to room temperature (about 25°C).
[0200] 4. Test execution:
[0201] Start the testing machine to perform the interface bonding strength test and record the maximum peel force or shear force of each sample.
[0202] Each sample was tested 3 times and the average value was taken.
[0203] The experimental data are shown in the following table:
[0204]
[0205]
[0206] This experiment compares the interfacial bonding strength of Examples 1-5 of the present invention with Comparative Examples 1-1 to 3-5, and further explores the role and effect of modified chemical coupling agents and plasma treatment in cork rubber metal composite materials. The data show that the examples of the present invention show significantly better bonding strength than the comparative examples in various tests.
[0207] 1. Effect of plasma treatment
[0208] From the data comparison between the embodiment and comparative example 1 (without plasma treatment), it can be seen that plasma treatment significantly improves the interfacial bonding strength of the material. For example, the average bonding strength of embodiment 1 is 8.6 N / mm, while the average bonding strength of comparative example 1-1 (the same material without plasma treatment) is only 6.3 N / mm. Plasma treatment enhances the activity of the material surface by introducing active functional groups (such as hydroxyl and carboxyl groups) on the material surface, thereby providing more anchor points for the coupling agent to react chemically with the material surface to form a more stable chemical bond.
[0209] 2. The role of modified chemical coupling agent
[0210] Comparing the results of the examples with those of comparative example 2 (using unmodified conventional coupling agents), the effect of the modified chemical coupling agent of the present invention is very significant. Taking Example 1 and Comparative Example 2-1 as examples, the bonding strength of Example 1 is 8.6 N / mm, while the bonding strength of Comparative Example 2-1 is 7.0 N / mm. The diisocyanate-based silicone oil component in the modified chemical coupling agent reacts with the rubber molecules in the rubber layer to form a reinforced cross-linked network, which not only improves the bonding strength of the bonding interface, but also increases the overall mechanical strength. The addition of polyethylene glycol and dimethyldiallylammonium chloride improves the wettability and diffusivity of the coupling agent, ensuring more uniform coating and more efficient chemical cross-linking.
[0211] 3. Necessity of coupling agent
[0212] By comparing the data of the embodiment and comparative example 3 (without any coupling agent), we can see the importance of coupling agents in improving the bonding strength. The bonding strength of embodiment 1 is much higher than that of comparative example 3-1 (5.5 N / mm), which shows that even after plasma treatment, the interface bonding is still weak without a coupling agent. The presence of a coupling agent is a key factor in ensuring that a stable chemical bond can be formed between materials.
[0213] The present invention successfully solves the problem of insufficient interfacial bonding of traditional cork-rubber-metal composite materials by introducing plasma surface treatment and modified chemical coupling agent technology. Plasma treatment improves the chemical activity of the material surface, and the modified chemical coupling agent significantly improves the interfacial bonding strength of the composite material and the mechanical properties of the overall structure by forming a stable chemical bond with the surface of each material. These innovations not only improve the performance of the product, but also enhance its application potential in harsh environments, providing important technical support for the industrial application of cork-rubber-metal composite materials.
[0214] Comparative experiment 2: tensile strength test
[0215] Experimental steps:
[0216] 1. Sample preparation:
[0217] Composite material samples were prepared according to the preparation process of Examples 1-5 and Comparative Examples 1-1 to 3-5, and the size of each sample was 100 mm x 20 mm x 5 mm.
[0218] 2. Sample installation:
[0219] Install the sample in the tensile test fixture of the universal material testing machine, ensuring that the sample is firmly fixed and the clamping part does not slip.
[0220] 3. Test condition settings:
[0221] The stretching speed was set to 5 mm / min.
[0222] The test temperature was set to room temperature (about 25°C).
[0223] 4. Test execution:
[0224] Start the testing machine to perform the tensile strength test and record the maximum tensile strength and elongation at break of each sample.
[0225] Each sample was tested 3 times and the average value was taken.
[0226] The experimental data are shown in the following table:
[0227]
[0228]
[0229]
[0230] According to the data of the tensile strength test, it is clearly shown that the embodiments of the present invention are superior to the comparative examples in all test indicators. This superior performance is mainly attributed to the modified chemical coupling agent and plasma treatment technology used in the present invention. The following is the specific analysis content:
[0231] 1. Effect of plasma treatment
[0232] From the data comparison between the embodiment and comparative example 1 (without plasma treatment), it can be seen that plasma treatment significantly improves the tensile strength of the material. For example, the average tensile strength of embodiment 1 is 25.8 MPa, while the average tensile strength of comparative example 1-1 (the same material without plasma treatment) is only 18.1 MPa. Plasma treatment enhances the chemical activity of the material surface by introducing active functional groups (such as hydroxyl and carboxyl groups) on the material surface. These active functional groups provide more anchor points for the coupling agent to form stable chemical bonds with the material surface, thereby improving the bonding strength of the interface and the overall mechanical strength.
[0233] 2. The role of modified chemical coupling agent
[0234] Comparing the results of the examples with those of comparative example 2 (using unmodified traditional coupling agents), the effect of the modified chemical coupling agent of the present invention is very significant. Taking Example 1 and Comparative Example 2-1 as examples, the tensile strength of Example 1 is 25.8MPa, while the tensile strength of Comparative Example 2-1 is 20.6MPa. The diisocyanate-based silicone oil component in the modified chemical coupling agent forms chemical crosslinks with the rubber molecules, enhancing the interfacial bonding strength and the overall mechanical properties of the material. The addition of polyethylene glycol improves the wettability and diffusivity of the coupling agent, ensuring that the coupling agent is evenly covered on the surface of the material, thereby forming a more stable interface bond. Dimethyldiallylammonium chloride acts as a catalyst to accelerate the coupling reaction and further improve the bonding strength.
[0235] 3. Necessity of coupling agent
[0236] By comparing the data of the examples with those of comparative example 3 (without any coupling agent), it can be seen that the coupling agent is important for improving the tensile strength. The tensile strength of Example 1 is 25.8MPa, while the tensile strength of comparative example 3-1 is only 15.3MPa. This shows that even with plasma treatment, the interface bonding is still weak without a coupling agent. The presence of a coupling agent is a key factor in ensuring that stable chemical bonds can be formed between materials. The coupling agent enhances the interfacial bonding strength by forming chemical bonds on the surfaces of different materials, significantly improving the overall mechanical properties of the composite material.
[0237] Comparative experiment 3: Fatigue life test
[0238] Experimental steps:
[0239] 1. Sample preparation:
[0240] Composite material samples were prepared according to the preparation process of Examples 1-5 and Comparative Examples 1-1 to 3-5, and the size of each sample was 100 mm x 20 mm x 5 mm.
[0241] 2. Sample installation:
[0242] Install the sample in the cyclic loading fixture of the fatigue testing machine, ensuring that the sample is firmly fixed and the clamping part does not slip.
[0243] 3. Test condition settings:
[0244] The loading frequency was set to 5 Hz.
[0245] The loading stress range was set from 50% of the maximum tensile strength to 10% of the maximum tensile strength.
[0246] The test temperature was set to room temperature (about 25°C).
[0247] 4. Test execution:
[0248] Start the fatigue testing machine to perform cyclic loading test and record the fatigue life (number of cycles) of each sample.
[0249] Each sample was tested 3 times and the average value was taken. The experimental results are shown in the following table:
[0250]
[0251]
[0252] It can be seen from the table that the embodiments of the present invention are significantly better than the comparative examples in terms of fatigue life, and the specific analysis is as follows:
[0253] 1. Effect of plasma treatment
[0254] From the data comparison between the embodiment and comparative example 1 (without plasma treatment), it can be seen that plasma treatment significantly improves the fatigue life of the material. For example, the average fatigue life of embodiment 1 is 205,000 times, while the average fatigue life of comparative example 1-1 is 122,333 times. Plasma treatment enhances the chemical activity of the material surface by introducing active functional groups (such as hydroxyl and carboxyl groups) on the material surface. These active functional groups provide more anchor points for the coupling agent to form stable chemical bonds with the material surface, thereby improving the bonding strength of the interface and the overall mechanical strength, and significantly extending the fatigue life of the material.
[0255] 2. The role of modified chemical coupling agent
[0256] Comparing the results of the examples with those of comparative example 2 (using unmodified traditional coupling agents), the effect of the modified chemical coupling agent of the present invention is very significant. Taking Example 1 and Comparative Example 2-1 as examples, the fatigue life of Example 1 is 205,000 times, while the fatigue life of Comparative Example 2-1 is 152,333 times. The diisocyanate-based silicone oil component in the modified chemical coupling agent forms chemical crosslinks with the rubber molecules, enhancing the interfacial bonding strength and the overall mechanical properties of the material. The addition of polyethylene glycol improves the wettability and diffusivity of the coupling agent, ensuring that the coupling agent is evenly covered on the surface of the material, thereby forming a more stable interface bond. Dimethyldiallylammonium chloride acts as a catalyst to accelerate the coupling reaction, further improving the bonding strength and fatigue life.
[0257] 3. Necessity of coupling agent
[0258] By comparing the data of the embodiment and comparative example 3 (without using any coupling agent), we can see the importance of coupling agents in improving fatigue life. The fatigue life of embodiment 1 is 205,000 times, while the fatigue life of comparative example 3-1 is only 91,000 times. This shows that even after plasma treatment, the interface bonding is still weak without a coupling agent. The presence of a coupling agent is a key factor in ensuring that stable chemical bonds can be formed between materials. The coupling agent forms chemical bonds on the surfaces of different materials, thereby enhancing the interfacial bonding strength and significantly improving the fatigue life of the composite material.
[0259] Comparative experiment 5: Thermal stability test
[0260] Experimental steps:
[0261] 1. Sample preparation:
[0262] Composite material samples were prepared according to the preparation process of Examples 1-5 and Comparative Examples 1-1 to 3-5, and the size of each sample was 20 mm x 20 mm x 5 mm.
[0263] 2. Thermogravimetric analysis (TGA):
[0264] The sample was placed in a thermogravimetric analyzer and heated from room temperature to 600°C at a heating rate of 10°C / min. The mass change of the sample was recorded to determine the thermal decomposition temperature (T_d).
[0265] 3. Differential Scanning Calorimetry (DSC):
[0266] The sample was placed in a differential scanning calorimeter and heated from room temperature to 300°C at a heating rate of 10°C / min. The heat flow change of the sample was recorded to determine the glass transition temperature (T_g) and melting temperature (T_m).
[0267] 4. High temperature oven thermal aging test:
[0268] The samples were placed in a high-temperature oven and aged at 150°C for 24 hours. After being taken out, mechanical properties were tested and the performance changes before and after thermal aging were recorded.
[0269] The experimental results are shown in the following table:
[0270] Thermogravimetric analysis (TGA) data
[0271]
[0272]
[0273]
[0274] Differential Scanning Calorimetry (DSC) Data
[0275]
[0276]
[0277]
[0278] High temperature oven thermal aging test data
[0279]
[0280] It can be clearly seen from the table data that the embodiments of the present invention are significantly better than the comparative examples in terms of thermal stability, and the specific analysis is as follows:
[0281] 1. Effect of thermal decomposition temperature (TGA)
[0282] From the data comparison between the embodiment and comparative example 1 (without plasma treatment), it can be seen that plasma treatment significantly increases the thermal decomposition temperature of the material. For example, the average thermal decomposition temperature of embodiment 1 is 412.7°C, while the average thermal decomposition temperature of comparative example 1-1 is only 352.3°C. Plasma treatment enhances the chemical activity of the material by introducing active functional groups on the surface of the material. These active functional groups provide more anchor points for the coupling agent to form stable chemical bonds with the surface of the material, thereby improving the thermal stability of the material.
[0283] 2. The role of glass transition temperature and melting temperature (DSC)
[0284] Comparing the results of the examples with those of comparative example 2 (using unmodified traditional coupling agents), the effect of the modified chemical coupling agent of the present invention is very significant. Taking Example 1 and Comparative Example 2-1 as examples, the average glass transition temperature of Example 1 is 86.0°C and the melting temperature is 251.0°C, while the average glass transition temperature of Comparative Example 2-1 is 76.0°C and the melting temperature is 231.0°C. The diisocyanate-based silicone oil component in the modified chemical coupling agent forms chemical crosslinks with the rubber molecules, enhancing the interfacial bonding strength and the overall mechanical properties of the material. The addition of polyethylene glycol improves the wettability and diffusivity of the coupling agent, ensuring that the coupling agent is evenly covered on the surface of the material, thereby forming a more stable interfacial bond. Dimethyldiallylammonium chloride, as a catalyst, accelerates the coupling reaction and further improves the bonding strength and thermal stability.
[0285] 3. Necessity of high temperature thermal aging test
[0286] By comparing the data of the examples with those of comparative example 3 (without any coupling agent), we can see the importance of coupling agents in improving thermal aging stability. The change in tensile strength before and after thermal aging of Example 1 was only -5.0%, while the change in comparative example 3-1 was -31.4%. This shows that even with plasma treatment, the interface bonding is still weak without a coupling agent. The presence of a coupling agent is a key factor in ensuring that stable chemical bonds can be formed between materials. The coupling agent forms chemical bonds on the surfaces of different materials, thereby enhancing the interfacial bonding strength and significantly improving the thermal aging stability of the composite material.
[0287] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A preparation process of a cork-rubber-metal composite material, characterized in that: The following steps are involved: S1. Clean metal, cork and rubber surfaces; S2, plasma treatment of metal, cork and rubber surfaces; S3, preparing a modified chemical coupling agent and applying it on metal, cork and rubber surfaces; S4, performing hot pressing forming, laminating the metal, rubber and cork and performing hot pressing treatment; S5. Cooling treatment to obtain the cork-rubber-metal composite material.
2. The preparation process of a cork-rubber-metal composite material according to claim 1, characterized in that: The metal surface cleaning treatment includes cleaning with an alkaline solution at a temperature of 20-30° C., followed by rinsing with distilled water.
3. The preparation process of a cork-rubber-metal composite material according to claim 1, characterized in that: The plasma treatment is performed using argon plasma, the treatment time is 1-3 minutes, and the power is set to 100-300W.
4. The preparation process of a cork-rubber-metal composite material according to claim 1, characterized in that: The modified chemical coupling agent comprises: 3-Methylpropanetriethoxysilane 70-80wt%; Diisocyanate silicone oil 10-20wt%; Polyethylene glycol 5-10wt%; Dimethyldiallylammonium chloride 2-5wt%.
5. The preparation process of the cork-rubber-metal composite material according to claim 4, characterized in that: The preparation method of the modified chemical coupling agent comprises: Mixing a silane coupling agent, a reinforcing agent, a surfactant and a catalyst according to a proportion; Stir the reaction at 70-90°C for 3-5 hours; After the reaction, the mixture is cooled to room temperature and filtered to obtain the modified chemical coupling agent.
6. The preparation process of a cork-rubber-metal composite material according to claim 1, characterized in that: The coupling agent application step comprises soaking the metal, cork and rubber in a coupling agent solution with a concentration of 1-3%, treating for 5-15 minutes, and then drying at room temperature for 1-2 hours.
7. The preparation process of a cork-rubber-metal composite material according to claim 1, characterized in that: The hot pressing step comprises: Arrange metal, rubber, and cork in stacking order; At a temperature of 140-180°C, a pressure of 4-8 MPa is applied for pressing for 10-20 minutes.
8. The preparation process of a cork-rubber-metal composite material according to claim 1, characterized in that: The cooling process is to cool naturally at room temperature to normal temperature.
9. The preparation process of a cork-rubber-metal composite material according to claim 1, characterized in that: The chemical bonds formed by the modified chemical coupling agent on the surfaces of metal, cork and rubber include complex bonds and covalent bonds.
10. The preparation process of a cork-rubber-metal composite material according to claim 1, characterized in that: The thickness of the cork-rubber-metal composite material after hot pressing is 2-10 mm.
Citation Information
Cited By
Insulating coating on side surface of resistor disc of lightning arrester and preparation method of insulating coating
CN120025700A
Non-metal and metal material gluing and curing method and system based on frequency conversion microwaves
CN120079572A
High-hardness silica gel strip and preparation method thereof
CN120209583A
